Production and opeartions management - Chunawalla, S.A.; Patel, D.R. (Mumbai, 2010)
Before the sub-prime crisis and the consequent failure of the overleveraged US and European banks, Indian economy was growing at a healthy 9 per cent, but the slow down brought the growth rate down to 6-6.5 per cent. However, it goes to India?s credit that when most of the economies abroad were showing negative growth, we continued to grow positively. The growth rate now hovers between 7 and 7.75 per cent. Indian manufacturing sector has also shown signs of recovery. Though China too continues to grow, China earns huge foreign exchange in dollar falls, the Chinese economy with a huge dollar the US treasury bills. If the rate of dollar falls, the Chinese economy with a huge dollar pile up is likely to suffer. Indian itself is a vast market, and our economy is not totally export-oriented. Indian banking sector is regulated by the RBI, and is not allowed risky exposures. Production and Operations Management is a vitally important area in a growing economy. This book explains the nuts and bolts of this subject in an easy-to-understand manner. The text is supported by supplementary materials given in boxes. The ancillary areas of purchasing, materials, stores and inventory are also covered in sufficient details. As manufacturing is slowly moving from being just labour intensive, new concepts such as CAD/CAM and automation have been dealt with. Manufacturing processes and being questioned through business process re-engineering which has been discussed. OR techniques like Waiting Lines, and Transportation Models have been added. The HE and financial aspects of production have not been left untouched. In short, this is comprehensive text of this subject, useful to students and practitioners. About The Author: About S.A.Chunawalla New Page 1 S.A. CHUNAWALLA is a writer and thinker on management subjects for more than a quarter of a century. He formerly taught management students in Gujarat. He has a good blend of techno-commercial academic background. He has guided stude
Keywords: MANAGEMENT; CAPITAL BUDGETING; INVENTORY MANAGEMENT; WAITING LINES; PERFORMANCE APPRAISAL